2014
DOI: 10.1371/journal.pone.0111734
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Assess the Feasibility of Transcutaneous Glomerular Filtration Rate Measurement Using Fluorescence-Labelled Sinistrin in Dogs and Cats

Abstract: In dogs and cats an assessment of renal function is often needed, however, existing methods including urine and plasma clearances are invasive, cumbersome and time consuming. This pilot study evaluated the feasibility of a transcutaneous glomerular filtration rate (GFR) measurement in dogs and cats. Additionally the optimal dose and location for the transcutaneous measurement device were investigated. Renal elimination of fluorescein-isothiocyanate-labelled sinistrin (FITC-S) was measured transcutaneously for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This method to assess renal function has been already validated in different species by comparison with the traditional approach of plasma clearance 9,11,12 . Following the protocol exposed here, Schreiber et al demonstrated the validity of the technique in different mouse models, showing highly comparable results among the transcutaneous measurement and plasma clearance for all the groups studied (Table 1) 9 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method to assess renal function has been already validated in different species by comparison with the traditional approach of plasma clearance 9,11,12 . Following the protocol exposed here, Schreiber et al demonstrated the validity of the technique in different mouse models, showing highly comparable results among the transcutaneous measurement and plasma clearance for all the groups studied (Table 1) 9 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…This adaptability of the method has already been confirmed by its successful application in different species of rodents and several types of strains with varied health conditions. In addition, the transcutaneous assessment of renal function has been recently validated in dogs and cats 12 with excellent results. Due to the undoubted differences between these animals and rodents, this study determined the appropriate dose of FITC-sinistrin for both, dogs and cats, and it performed a much longer measuring time, 4 hours instead of the 1 or 2 hours used in rodents.…”
Section: As Shown Inmentioning
confidence: 99%
“…This technique allows noninvasive, real‐time monitoring of the elimination kinetics of an injected tracer to measure plasma clearance. These methods are currently under development and successful use of fluorescent GFR markers including carboystyril124‐DTPA‐europium and FITC‐sinistrin to measure kidney function in different animal models has been reported .…”
Section: Novel Methods Of Measuring Kidney Functionmentioning
confidence: 99%
“…67,68,72 These later studies were accomplished using a transcutaneous fluorescence excitation emitter and an emission monitor that detects ECF fluorescence through the skin. Transcutaneous detection of fluorescent sinistrin has also been used in cats and dogs 73 , and a detector that allows continuous monitoring has been developed for use in awake mice. 74 Non-fluorescent sinistrin has been successfully used safely in humans with various levels of kidney function, including patients with augmented renal clearance.…”
Section: Translating Fluorescence Measurements Into Clinical Observatmentioning
confidence: 99%